Penerapan Model Improve Learning untuk Meningkatkan Hasil Belajar pada Pembelajaran Pendidikan Agama Islam - Nur Qoyyimah; Febrilia Nurhayati; Darul Istianah; Luluk Musayyaroh; Siti Nuranisah; M. Kharisbudiman (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Learning outcomes in the learning process play a crucial role in building a strong academic foundation and developing essential life skills for the future. One of the instructional models that can foster these abilities is the Improve Learning model. The purpose of this study is to describe the steps, strengths, and weaknesses of implementing the Improve Learning model in Islamic Religious Education (PAI) learning at Madrasah Aliyah Negeri (MAN) 2 Rembang and MAN 1 Kebumen. This study uses a qualitative approach. The research subjects are teachers at MAN 2 Rembang and MAN 1 Kebumen. The informants are Islamic Religious Education teachers. Data collection techniques include interviews, observations, and documentation. The results of the study are: (1) The steps of the Improve Learning model consist of Introducing, Modeling, Practicing, Reflecting, Applying, Validating, and Evolving; (2) The strengths of the Improve Learning model include encouraging students to think critically, training reflective and evaluative skills, facilitating meaningful and sustainable learning, enhancing problem-solving abilities, and increasing students’ motivation and learning independence; (3) The weaknesses of the Improve Learning model are that it requires a relatively long time, demands teacher readiness and skills, and is less suitable for passive students or those with low motivation. The conclusion of this study is that the Improve Learning model can be applied in the learning process as an effort to improve learning outcomes at MAN 2 Rembang and MAN 1 Kebumen.